iPhone sensor platforms: Applications to sports monitoring - McNab, T.; James, D. A.; Rowlands, D. (Procedia Engineering, 2011)
The testing and monitoring of elite athletes in their natural training environment is becoming an area of interest to the sporting community. Specialised equipment is cumbersome and influences the training and analysis regimens athletes undertake to improve their performance. Ubiquitous and off-the-shelf versatile smartphones with advanced sensing capabilities can be applied to sports activity monitoring, providing a cost-effective means of widespread performance analysis. This paper briefly outlines the case for using these smartphones in sports monitoring applications, presents a model to collect data generated by these devices and presents the results of real-world usage when applied to cricket.